2015
DOI: 10.3389/fnins.2015.00458
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Functional Significance of Stroke-Induced Neurogenesis

Abstract: Stroke affects one in every six people worldwide, and is the leading cause of adult disability. After stroke, some limited spontaneous recovery occurs, the mechanisms of which remain largely unknown. Multiple, parallel approaches are being investigated to develop neuroprotective, reparative and regenerative strategies for the treatment of stroke. For years, clinical studies have tried to use exogenous cell therapy as a means of brain repair, with varying success. Since the rediscovery of adult neurogenesis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 202 publications
(270 reference statements)
0
54
0
Order By: Relevance
“…These activated microglia, in turn, release TNF-α, which induces neuron apoptosis in a caspase-3 dependent pathway [70]. There is a growing body of evidence that many neuronal subpopulations express TLRs, including TLR4 [132][133][134][135]. Mice with a defect in TLR4 are generally more resistant to CNS trauma [62], suggesting that TLR4 activation is detrimental to neuronal survival.…”
Section: Neuronsmentioning
confidence: 99%
“…These activated microglia, in turn, release TNF-α, which induces neuron apoptosis in a caspase-3 dependent pathway [70]. There is a growing body of evidence that many neuronal subpopulations express TLRs, including TLR4 [132][133][134][135]. Mice with a defect in TLR4 are generally more resistant to CNS trauma [62], suggesting that TLR4 activation is detrimental to neuronal survival.…”
Section: Neuronsmentioning
confidence: 99%
“…Recent studies showed that the brain possesses the ability to generate newly born cells from stem or neural progenitor cells in the subventricular zone and subgranular zone of the dentate gyrus. It was reported that division of these cells in the adult brain was enhanced by ischemic injuries, and newly produced cells became integrated in the neural network and participated in recovery [1][2][3] . In contrast to the adult brain, published data about endogenous regeneration in the developing rodent brain after ischemic injury are conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…After acute ischemia, proliferation of these, and other, progenitor cells in the CNS is enhanced [88,136,137], and, similarly, shorter pulses of ischemia to induce preconditioning effects also result in the proliferation of progenitors [137,138], with an increase of up to 4-fold observed after preconditioning in one study [137]. Interestingly, when prolife r a t i o n w a s a t t e n u a t e d b y a d m i n i s t r a t i o n o f methylazoxymethanol acetate or ganciclovir, the preconditioning effect of a short ischemic event (15 min MCAO) was abolished [137].…”
Section: Progenitor Cellsmentioning
confidence: 99%
“…Adult neurogenesis occurs in well-characterized neurogenic niches, such as the subventricular zone of the lateral ventricle and the subgranular zone of the dentate gyrus in the hippocampus, in both the normal adult brain and the ischemia-injured brain [136]. After acute ischemia, proliferation of these, and other, progenitor cells in the CNS is enhanced [88,136,137], and, similarly, shorter pulses of ischemia to induce preconditioning effects also result in the proliferation of progenitors [137,138], with an increase of up to 4-fold observed after preconditioning in one study [137].…”
Section: Progenitor Cellsmentioning
confidence: 99%